Implementación del proceso de elaboración de cerveza a partir de pitahaya amarilla (Hylocereus megalanthus) y evaluación de calidad - Pelaez Chango, Gabriela Lizbeth (2023)
Food industrialization plays a vital role in reducing hunger by preventing product losses. One of the most prominent fruits currently and with the most promising future in Ecuador is the pitahaya, which nowadays has not been used to its full potential and innovation in the processing of its derivatives, which holds interest and industrial relevance. The objective of the current study was to select and implement the brewing process of yellow pitahaya (H. megalanthus) by assessing its physical-chemical and organoleptic properties. Pitahaya fruits that were not optimal for commercialization were used. The fruit was brought from Palora canton in Morona Santiago province. Two methods of separating the seed from the fruit were evaluated: mechanical (physical) separation and thermal mash, once the most suitable was determined, the pitahaya beer was prepared with different proportions of the fruit (1:3, 1:4, 1:6). Subsequently, physical-chemical parameters (pH, titratable acidity, degrees of alcohol, IBUs and color) and organoleptic (visual, olfactory and taste analysis) were evaluated. The results suggest that the best method to separate the seed is thermal mash versus mechanical separation. The physical-chemical results obtained were: in the analysis of alcohol by volume 5.5 %, an average pH of 4.4, 0.096 of titratable acidity, 26.3 IBUs and 5 SRM. Regarding organoleptic properties, the beer with a 1:4 ratio was the best score in the tasting carried out by certified judges. In conclusion, pitahaya has the potential to be a perfect base for brewing beer, furthermore, pitahaya fruit contains phytoalbumins that help as a natural clarifier and stabilizer. Keywords: food losses, rejection fruits, pitahaya, industrialization, beer.